Ginkgolide B Blocks Vascular Remodeling after Vascular Injury via Regulating Tgfβ1/Smad Signaling Pathway - Quan Wang; Shuai Ni; Li Ling; Siqi Wang; Hanbin Xie; Zhanhong Ren (Cardiovascular Therapeutics)
Coronary artery disease (CAD) is the most prevalent cardiovascular disease worldwide, resulting in myocardial infarction (MI) and even sudden death. Following percutaneous coronary intervention (PCI), restenosis caused by vascular remodeling is always formed at the stent implantation site. Here, we show that Ginkgolide B (GB), a naturally occurring terpene lactone, effectively suppresses vascular remodeling and subsequent restenosis in wild-type mice following left carotid artery (LCA) injury. Additional experiments reveal that GB exerts a protective effect on vascular remodeling and further restenosis through modulation of the Tgfβ1/Smad signaling pathway in vivo and in human vascular smooth muscle cells (HVSMAs) but not in human umbilical vein endothelial cells (HUVECs) in vitro. Moreover, the beneficial effect of GB is abolished after incubated with pirfenidone (PFD, a drug for idiopathic pulmonary fibrosis, IPF), which can inhibit Tgfβ1. In Tgfβ1-/- mice, treatment with pirfenidone capsules and Yinxingneizhi Zhusheye (including Ginkgolide B) fails to improve vascular remodeling and restenosis. In conclusion, our data identify that GB could be a potential novel therapeutic agent to block vessel injury-associated vascular remodeling and further restenosis and show significant repression of Tgfβ1/Smad signaling pathway.